Readmission Events Following EGD for Upper Gastrointestinal Bleed: An Analysis Using the National Readmission Database - Vignesh Krishnan Nagesh; Vivek Joseph Varughese; Jaber Musalli; Gomathy Aarthy Nageswaran; Erin Russell; Susan Anne Feldman; Simcha Weissman; Adam Atoot (Medical Sciences)
Background: Upper Gastrointestinal Bleed (UGIB) is a common and potentially life-threatening condition with an annual incidence of 80–150 per 100,000 individuals and a mortality rate of 2–10%. Esophagogastroduodenoscopy (EGD) is the gold standard for both diagnosis and treatment, but post-discharge outcomes, including readmissions, remain underexplored. Methods: This study utilized the 2021 National Readmission Database (NRD) to analyze 30-day readmission rates following EGD for UGIB. Adult patients (≥18 years) admitted for UGIB and undergoing EGD were included; those who died during the index hospitalization were excluded. Demographic, clinical, and socioeconomic factors associated with readmission were examined using multivariate logistic regression. Results: Among 34,257 patients admitted for UGIB and undergoing EGD, 11,088 (32.4%) were readmitted within 30 days, with 5423 (49%) due to recurrent UGIB. Readmitted patients had a higher mean age (68.46 vs. 67.63 years) and greater prevalence of cirrhosis (16.71% vs. 13.84%). Hospital resource utilization was significantly higher among readmissions, with increased total hospital charges (USD 82,544.82 vs. USD 61,521.17) and longer hospital stays (5.38 vs. 4.97 days). Mortality was lower among readmitted patients (1.46% vs. 3.53%). Multivariate analysis identified cirrhosis (OR 7.20, 95% CI: 6.45–8.02), untreated H. pylori infection (OR 3.43, 95% CI: 2.15–4.30), atrial fibrillation (OR 1.52, 95% CI: 1.36–1.69), and chronic antithrombotic therapy (OR 1.63, 95% CI: 1.41–1.89) as significant predictors of recurrent UGIB readmission. Lower socioeconomic status was also associated with increased readmission risk (OR 1.15, 95% CI: 1.05–1.25). Conclusions: Readmission following EGD for UGIB is common and driven primarily by recurrent bleeding. Cirrhosis, untreated H. pylori infection, atrial fibrillation, and chronic anticoagulation therapy are key risk factors. These findings highlight the need for targeted interventions, including improved post-discharge management and optimization of anticoagulation strategies, to reduce readmission rates and improve patient outcomes.